Creating a staff-led strategic plan : a practical guide for libraries - Mathuews, Katy B.; Spellman, Ryan A. (New York : Bloomsbury Libraries Unlimited, 2023)
'Taking a staff-led approach, this book helps libraries of all types create their own meaningful and authentic strategic plans while demystifying a process that can bring many benefits to the organization'--
'With dwindling budgets to pay for consultants and a growing interest in collaboration across the organization, libraries are increasingly taking a do-it-yourself approach to strategic planning.This book takes a step-by-step approach to grassroots strategic planning for libraries of all types. The authors, who led a successful strategic planning process at their own library, provide practical advice and detailed information to guide library personnel through their own process. Topics include aligning with institutional and community values, creating vision and mission statements, researching stakeholder needs, conducting environmental scans, collaborative drafting of the plan, communication strategies, and implementation and assessment of the plan. Each chapter helps librarians create a strategic plan for a broad spectrum of libraries, including K-12, post-secondary, public, and special libraries. A unique feature of the book is its emphasis on the ways in which different library types can collaborate to meet shared goals.This book is a one-stop-shop, providing everything library staff will need to create a strategic plan without searching for additional sources'--
Part I. Pre-Project Planning -- Understanding Strategic Planning -- Laying the Foundation for a Staff-Led Approach -- Part II. Creating the Plan -- Research and Data Analysis -- Writing your strategic plan -- Part III. Implementing the Plan -- Creating, implementing, and Assessing Initiatives -- Communicating Throughout and Beyond the Planning Process -- Appendices. Sample Library Strategic Plans -- Appendix A. Athens County Public Libraries Strategic Plan, 2016-2019 : Building on Success -- Appendix B. Calgary Public Library Strategic Plan, 2019-2022 : Potentials Realized -- Appendix C. Ohio University Libraries Strategic Plan, 2021-2023 -- Appendix D. The University of Texas Rio Grande Valley, University Library Strategic Plan, 2018-2021 -- Appendix E. Busitema University Library Strategic Initiatives, January 2021-December 2022, Excerpt : GOAL 7, Build a Robust Assessment Programme -- Appendix F. Forbes Library Strategic Plan, 2019-2023 -- Index.
Includes bibliographical references and index.
Keywords: Library planning; Strategic planning; Library administration -- Employee participation